Dependence of drift rate of radio bursts on frequencies for the period of solar activity 2019-2020 - Damdin, Batmunkh; Batmunkh, Batbayar; Monstein, Christian (Mongolian Journal of Astronomy and Geophysics, 2024)
In this paper, we calculated the frequency drift rate (df/dt) of radio bursts observed at the minimum of solar activity of the 25th cycle. The observational spectra of radio bursts from the "CALLISTO network" database were used. The calculation was carried out for the spectra recorded on April 13, 2019 and March 8, 2020. The calculated frequency drift rate were described as df/dt ≃ afb and the code nonlinear least-squares fit "Marquardt’s method" as used to determine the constants (a,b). It is shown that these parameters can be used to determine the electron density of the solar corona.